Genomic analysis of Listeria monocytogenes from US food processing environments reveals a high prevalence of QAC efflux genes but limited evidence of their contribution to environmental persistence - Daeschel, Devin; Pettengill, James B.; Wang, Yu; Chen, Yi; Allard, Marc; Snyder, Abigail B. (BMC genomics, 2022)
Quaternary ammonium compound (QAC) efflux genes increase the minimum inhibitory concentration of Listeria monocytogenes (Lm) to benzalkonium chloride sanitizer, but the contribution of these genes to persistence in food processing environments is unclear. The goal of this study was to leverage genomic data and associated metadata for 4969 Lm isolates collected between 1999 and 2019 to: (1) evaluate the prevalence of QAC efflux genes among Lm isolates from diverse US food processors, (2) use comparative genomic analyses to assess confounding factors, such as clonal complex identity and stress tolerance genotypes, and (3) identify patterns in QAC efflux gene gain and loss among persistent clones within specific facilities over time. The QAC efflux gene cassette bcrABC was present in nearly half (46%) of all isolates. QAC efflux gene prevalence among isolates was associated with clonal complex (ð.sup.2 < 0.001) and clonal complex was associated with the facility type (ð.sup.2 < 0.001). Consequently, changes in the prevalence of QAC efflux genes within individual facilities were generally attributable to changes in the prevalence of specific clonal complexes. Additionally, a GWAS and targeted BLAST search revealed that clonal complexes with a high prevalence of QAC efflux genes commonly possessed other stress tolerance genes. For example, a high prevalence of bcrABC in a clonal complex was significantly associated with the presence of the SSI-1 gene cluster (p < 0.05). QAC efflux gene gain and loss were both observed among persistent populations of Lm in individual facilities, suggesting a limited direct role for QAC efflux genes as predictors of persistence. This study suggests that although there is evidence that QAC efflux genes are part of a suite of adaptations common among Lm isolated from some food production environments, these genes may be neither sufficient nor necessary to enhance persistence. This is a crucial distinction for decision making in the food industry. For example, changes to sanitizer regimen targeting QAC tolerance would not address other contributing genetic or non-genetic factors, such as equipment hygienic design which physically mediates sanitizer exposure.